Fibroblast growth factor signals regulate transforming growth factor‐β‐induced endothelial‐to‐myofibroblast transition of tumor endothelial cells via Elk1. Issue 8 (19th June 2019) - Akatsu, Yuichi; Takahashi, Naoya; Yoshimatsu, Yasuhiro; Kimuro, Shiori; Muramatsu, Tomoki; Katsura, Akihiro; Maishi, Nako; Suzuki, Hiroshi I.; Inazawa, Johji; Hida, Kyoko; Miyazono, Kohei; Watabe, Tetsuro
Abstract : The tumor microenvironment contains various components, including cancer cells, tumor vessels, and cancer‐associated fibroblasts, the latter of which are comprised of tumor‐promoting myofibroblasts and tumor‐suppressing fibroblasts. Multiple lines of evidence indicate that transforming growth factor‐β (TGF‐β) induces the formation of myofibroblasts and other types of mesenchymal (non‐myofibroblastic) cells from endothelial cells. Recent reports show that fibroblast growth factor 2 (FGF2) modulates TGF‐β‐induced mesenchymal transition of endothelial cells, but the molecular mechanisms behind the signals that control transcriptional networks during the formation of different groups of fibroblasts remain largely unclear. Here, we studied the roles of FGF2 during the regulation of TGF‐β‐induced mesenchymal transition of tumor endothelial cells (TECs). We demonstrated that auto/paracrine FGF signals in TECs inhibit TGF‐β‐induced endothelial‐to‐myofibroblast transition (End‐MyoT), leading to suppressed formation of contractile myofibroblast cells, but on the other hand can also collaborate with TGF‐β in promoting the formation of active fibroblastic cells which have migratory and proliferative properties. FGF2 modulated TGF‐β‐induced formation of myofibroblastic and non‐myofibroblastic cells from TECs via transcriptional regulation of various mesenchymal markers and growth factors. Furthermore, we observed that TECs treated with TGF‐β were more competent in promoting in vivo tumor growth than TECs treated with TGF‐β and FGF2. Mechanistically, we showed that Elk1 mediated FGF2‐induced inhibition of End‐MyoT via inhibition of TGF‐β‐induced transcriptional activation of α‐smooth muscle actin promoter by myocardin‐related transcription factor‐A. Our data suggest that TGF‐β and FGF2 oppose and cooperate with each other during the formation of myofibroblastic and non‐myofibroblastic cells from TECs, which in turn determines the characteristics of mesenchymal cells in the tumor microenvironment. Abstract : Heterogeneous populations of tumor endothelial cells consisting of at least two different subgroups undergo transforming growth factor‐β (TGF‐β)‐stimulated endothelial‐to‐myofibroblast transition (End‐MyoT) and endothelial‐to‐non‐myofibroblast transition, which give rise to α‐smooth muscle actin (α‐SMA)‐positive myofibroblast‐like cells and α‐SMA‐negative fibroblastic cells, respectively. The stromal components containing α‐SMA‐positive cells become contractile and can promote tumor formation. Fibroblast growth factor 2 (FGF2) suppresses the effects of TGF‐β to induce End‐MyoT by suppressing α‐SMA expression. The stromal components contain active fibroblastic cells and become less potent at promoting tumor formation.